ANALISIS LAPORAN KEUANGAN BAZAR KEWIRAUSAHAAN PRODUK KREATIF LIMBAH K5PBB MAHASISWA PROGRAM STUDI PENDIDIKAN AKUNTANSI UNIVERSITAS PGRI PALEMBANG - Lestari, Neta Dian; Toyib, Muhammad (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
Facing the business challenges of MEA Era is a challenge that should be faced by us, as an Educator I feel compelled to be able to participate in the success of my students, to face the challenge. The purpose of this study is not only for the Financial Statements of Bazaar, but also seek emphasis on the experience of an entrepreneurial process because through the Bazaar students are required to interact with people, how to offer well and politely to consumers, convince consumers to buy the products they offer and give explanation and the best service for consumers to be satisfied. Based on the result of observations which are conducted by the researcher as many as 15 times, SWOT observation analysis is with an average amount of 65.5% in GOOD Category. The results of financial statements analysis each group to see three important elements are: Elements Report L /R with the percentage of 56.09% High category, Elements of Capital Changes with the percentage of 78.05% Very High category, and Element Balance with the percentage of Current Assets 63.67%, High category, Fixed Assets 14.38% Low category and Liability 78.05% Very High category. This bazaar activity is very useful for students to gain experience and learning to become entrepreneurs. This activity is a very useful activity for students especially students of Accounting Education Studies Program FKIP University PGRI Palembang. By doing this activity, the students are expected to know how to offer and market a product that they make themselves well, and students can know more how to interact well and politely with consumers or customers.